2014
DOI: 10.1038/ismej.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

The ambrosia symbiosis is specific in some species and promiscuous in others: evidence from community pyrosequencing

Abstract: Symbioses are increasingly seen as dynamic ecosystems with multiple associates and varying fidelity. Symbiont specificity remains elusive in one of the most ecologically successful and economically damaging eukaryotic symbioses: the ambrosia symbiosis of wood-boring beetles and fungi. We used multiplexed pyrosequencing of amplified internal transcribed spacer II (ITS2) ribosomal DNA (rDNA) libraries to document the communities of fungal associates and symbionts inside the mycangia (fungus transfer organ) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 68 publications
4
113
4
1
Order By: Relevance
“…These results could be due to the known problems of using ITS markers with certain groups of ambrosial fungi (Fraedrich et al 2008;Kostovcik et al 2015). Ceriani-Nakamurakare et al (2016), using a culture dependent approach, reported Raffaelea arxii and three additional Raffaelea species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results could be due to the known problems of using ITS markers with certain groups of ambrosial fungi (Fraedrich et al 2008;Kostovcik et al 2015). Ceriani-Nakamurakare et al (2016), using a culture dependent approach, reported Raffaelea arxii and three additional Raffaelea species.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing number of studies suggest that certain beetle species can have multiple fungal associates (Batra 1966;Gebhardt et al 2004;Ceriani-Nakamurakare et al 2016). Moreover, Kostovcik et al (2015) suggested that the ambrosia interaction is ecologically dynamic and more species-rich than any other insect-fungus interaction. Ceriani-Nakamurakare et al (2016) characterized the fungal community associated with M. mutatus and Populus deltoides based on culture dependent methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ambrosia beetles carry more than one fungal partner and these fungi are often isolated together (Carrillo et al 2014, Kostovcik et al 2015. The association of ophiostomatalean fungi with C.…”
Section: Discussionmentioning
confidence: 99%
“…The movement of symbionts amongst ambrosia beetle species had been recognized previously [69,71,73,74]. However, the magnitude and speed with which this has occurred for R. lauricola is unprecedented [70].…”
Section: Vectors Of Raffaelea Lauricolamentioning
confidence: 99%